Evidence in Civil Law - Poland - Bagan-Kurluta, Katarzyna (Law & Society, 2015)
The text presents legal issues concerning evidence and evidence taking in Polish civil proceedings. General principles of Polish civil proceedings are discussed, as well as the principles concerning evidence. The evolution of Polish proceedings is obvious: it is getting more and more formal. The provisions about preclusion are presented in this context and the contradictory model of the proceedings is expressed strongly. There are some doubts if the evolution of Polish Code of Civil Proceedings goes in right direction. The problem of possible adoption of pre-trial regulations is also mentioned.